Abdominal Actinomycosis Mimicking Malignancy: A Case Report - Rajani Gubbala; Ponnuswamy Arumugam; Suseela Kodandapani; Thammineedi Subramanyeshwar Rao (Amrita Journal of Medicine)
Actinomycosis is an uncommon chronic granulomatous disease caused by filamentous, gram-positive anaerobic bacteria. Actinomyces Israeli is the major human pathogen. They are commensal inhabitants of the oral cavity and intestinal tract but acquire invasion of breached or necrotic tissue. We report a 34-year-old female with intra-abdominal actinomycosis with extensive involvement of abdomen mimicking malignancy. She presented with abdominal pain and mass post laparoscopic cholecystectomy and underwent multiple biopsies which were inconclusive and was treated with antimicrobials with no relief. She was referred to our center suspecting malignancy. Biopsy was repeated and histopathology with special stains revealed actinomycosis. She was treated with intravenous crystalline penicillin of 6 million units thrice daily as an inpatient for a week. She was discharged on oral amoxicillin 1 g twice daily. The total antibiotic duration was 12 months since she had extensive disease. She was on regular follow-up and her lesions gradually regressed.